Gas-solid interaction of H-2-Ce0.95Zr0.05O2: new insights into surface participation in heterogeneous catalysis - Jain, Ruchi; Dubey, Anjani; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Catalysis Science & Technology, 2016)
A direct interaction between a reduction medium (H-2) and a Ce0.95Zr0.05O2 (CZ) solid surface was explored through ambient pressure photoelectron spectroscopy (APPES), with conventional X-ray and He-I photon sources, in H-2 atmosphere up to 0.1 mbar pressure and 773 K. A porous CZ thin film was prepared by a combination of sol-gel and spin-coating methods, and was employed to understand the redox nature of ceria under reduction conditions. The maximum of 45% Ce3+ along with the corresponding oxygen vacancy was observed due to reduction. An unprecedented decrease in the valence band (VB) energy up to 1.4 eV was observed on reduction along with a narrowing of VB. The highest occupied energy band derived from Ce 4f also shifts closer to E-F. H-2 molecular vibration observed in VB-APPES was employed as a probe to explore the surface potential changes along with the dynamic change in the nature of the surface under reduction conditions. The surface potential decreases by 0.27 eV up to 673 K, and then it reverts by 0.24 eV on further reduction at 773 K for different reasons. Further, an enhancement in the Ce 5d-O 2p interaction occurs at the expense of the Ce 4f-O 2p interaction under the above reduction conditions. Vacuum annealing and H-2 reduction after that show significantly more VB shift and enhanced reduction than H-2 reduction alone. Although Ce reduction occurs on high temperature vacuum annealing of CZ, a significantly lower amount of oxygen vacancies appears. This study shows the dynamic changes in the nature of the surface due to a gas (H-2)-solid (CZ) interaction and ensuing electronic structure changes that influence heterogeneous catalysis. It also underscores the necessity to study the catalytic materials under in situ conditions or closer to that.

Gas-solid interactions with reactive and inert gas molecules by NAPUPS: can work function be a better descriptor of chemical reactivity? - Ghosalya, Manoj Kumar; Reddy, Kasala Prabhakar; Mhamane, Nitin B.; Ranjan, Ravi; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2020)
The gas-phase vibrational spectra of reactive (H(2)and O-2) and inert gases (N(2)and Ar) have been studied by near-ambient pressure (NAP) ultraviolet photoelectron spectroscopy (NAPUPS) up to 0.3 mbar pressure. The results obtained are divided into two parts and discussed. In the first part, the photoelectron spectra of monoatomic Ar and some homonuclear diatomic molecules, such as H-2, O-2, and N-2, have been recorded by NAPUPS and the effect of pressure on their energy position has been studied. It has been demonstrated that NAPUPS could be an essential tool to determine the intermolecular or interatomic interactions. In the second part, we have evaluated the influence of different solid surfaces on the binding energy (BE) position, the pattern of the vibrational features of diatomic N(2)molecules, and the first atomic levels (3p(3/2)and 3p(1/2)) of monoatomic Ar. It has been observed that with a change in the (electronic/chemical) nature of the surface, the BE of the above features also changes and reflects the change in the work function (phi) of the material. It is to be noted that Ar is an inert/noble gas and N(2)is the most stable molecule, and the above changes observed underscore that they can be employed as probe atoms/molecules to explore even the minor changes that occur on a solid surface due to a variety of reasons. Further, if the solid surface undergoes any chemical/electronic changes due to gas-solid interaction, such as oxidation/reduction, the phi of the surface changes again; this highlights the precise identification of the changes that occur under the reaction/measurement conditions. Therefore, the change in the BE of the gas-phase features can be used to determine even the minor changes in the phi of solid surfaces during the reaction or due to the reaction. The present findings have implications in probing the surface changes that occur in any surface-dependent phenomena, such as heterogeneous catalysis, electrochemistry, and materials that are predominantly controlled by surface contribution, such as layered (2D) materials, nanomaterials.